(untitled) (مجلة إحالات, 2026)
The article aims to identify the characteristics of poetry during the first yaers of islam as well as the strong and weak side of the artistic aspect of poetry in a society where prose can be as poetry and which has not been weakened by the advent of islam. this new religion cames in order to improve it .new themes were appeared that have relation with the new life also the ancient terms declined in poetry. Islamic and pre-islamic one are different however there is a great relation between them (islamic poetry keeps old traces) which demonstrate the progress of poetry, using the descriptive analytical type.